1986
DOI: 10.1002/cber.19861191025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of benzo[1,2‐b′:4,5‐b′]dithiophene and its 4,8‐Dimethoxy and 4,8‐dimethyl derivatives

Abstract: Syntbese von Benzo[l,Zb: 4,5b']ditbiopben und seinen 4,tt-Dimetboxy-und 4,SDimetbyl-Derivaten Eine einfache Synthese fiir Benzo[ 1,2-b: 4,5-b']dithiophen (4) und die Synthese seines bisher unbekannten 4,8-Dimethoxy-(7) und 4,8-Dimethylderivates (13) wird beschrieben. IR-, 'H-NMR-, UVund MS-Daten werden mitgeteilt.In our group a large number of polyheteroarylenealkenylenes') with thiophene units were synthesized and their electrical conducting properties studied. In connection with this work, we also became int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…It ( Scheme 6 a) successfully realized double thiophene-ring annulation in good yields. On the other hand, 4,8-disubstituted derivatives ( 17c [ 55a ] and 17d [ 62 ] ) were also effectively synthesized from BDT-4,8-dione, [ 66 ] which could be prepared from commercially available 3-thiophene carboxylic acid (Scheme 6 b). Selective syntheses of the angular-shaped isomers ( 22 and 23 ) were achieved from 2-or 3-thiophene aldehyde, respectively (Scheme 6 c,d).…”
Section: Discussionmentioning
confidence: 99%
“…It ( Scheme 6 a) successfully realized double thiophene-ring annulation in good yields. On the other hand, 4,8-disubstituted derivatives ( 17c [ 55a ] and 17d [ 62 ] ) were also effectively synthesized from BDT-4,8-dione, [ 66 ] which could be prepared from commercially available 3-thiophene carboxylic acid (Scheme 6 b). Selective syntheses of the angular-shaped isomers ( 22 and 23 ) were achieved from 2-or 3-thiophene aldehyde, respectively (Scheme 6 c,d).…”
Section: Discussionmentioning
confidence: 99%
“…11 The decomposition of 16 is lower than those of 17 and 18, this result can be explained due to less thermal stability of benzo [1,2- 17 and 18 showed that all of the three oligomers are crystalline and it is expected that their thin films are well ordered under heat treatment.…”
Section: Resultsmentioning
confidence: 79%
“…The preparation of 2,6-dibromobenzo[1,2-b:4,5-b']dithiophene 11 17 and 2,9-dibromoanthracene 14 18 were synthesized according to literature procedures, respectively (Scheme 2). The 2,6-dibromonaphthalene 15 was purchased from Alfa Aesar Co.…”
Section: Resultsmentioning
confidence: 99%
“…The first syntheses of anti-BDT 1 reported by Kossemehl et al 17 and Katz et al 18 are based on thiophene derivatives as precursors. Other synthetic routes start from the functionalized benzene core 3a with TMS-acetylene via palladium catalyzed Cassar-Heck-Sonogashira coupling, 19 followed by intramolecular cyclization (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%